Occupational, academic, and personal determinants of wellbeing and psychological distress in residents: results of a survey in Lyon, France - Nohales, Ludivine; Fort, Emmanuel; Pelloux, Sophie; Coste, Clio; Leblanc, Pierre; De Ternay, Julia; Wallon, Martine; Rolland, Benjamin; Fassier, Jean-Baptiste; , BASIL Study Group; , SYREL MG; , SAIHL; et al. (Frontiers in Psychology, 2024)
Introduction: The mental health of residents is a growing significant concern, particularly with respect to hospital and university training conditions. Our goal was to assess the professional, academic, and psychological determinants of the mental health status of all residents of the academy of Lyon, France. Material and methods: The Health Barometer of Lyon Subdivision Residents (BASIL) is an initiative which consists in proposing a recurrent online survey to all residents in medicine, pharmacy, and dentistry, belonging to the Lyon subdivision. The first of these surveys was conducted from May to July 2022. Participants should complete a series of validated questionnaires, including the Warwick-Edinburgh Mental Wellbeing Scale (WEMWBS), and the Kessler Psychological Distress Scale (K6), respectively) and ad-hoc questions assessing their global health and hospital and academic working conditions. A Directed Acyclic Graph (DAG) analysis was conducted prior to multivariable analyses, to explore the determinants associated with low well-being (WEMWBS <43) and high psychological distress (K6 >= 13). Results: 904 residents (response rate: 46.7%) participated in the survey. A low level of well-being was observed in 23% of participants, and was significantly associated to job strain (OR = 2.18; 95%CI = [1.32-3.60]), low social support (OR = 3.13; 95%CI = [2.05-4.78]) and the experience of very poor university teaching (OR = 2.51; 95CI = [1.29-4.91]). A high level of psychological distress was identified for 13% of participants, and associated with low social support (OR = 2.41; 95%CI = [1.48-3.93]) and the experience of very poor university teaching (OR = 2.89, 95%CI = [1.16- 7.21]). Conclusion: Hospital working conditions, social support, and the perception of teaching quality, were three major determinants of well-being and psychological distress among health profession residents. Demographic determinants, personal life and lifestyle habits were also associated. This supports a multilevel action in prevention programs aiming to enhance well-being and reduce mental distress in this specific population and local organizational specificities.